Vegetation and climate dynamics in a 16,600-year marine sequence offshore Mozambique in Delagoa Bight, south-eastern Africa - F.H. Neumann; J. Finch; A. Hahn; C.S. Miller; L. Scott; E. Schefuß; L. Dupont; H.C. Cawthra; F. Engelbrecht (Quaternary International, 2025)

Disjunct resident population of Melodious Lark Mirafra cheniana discovered in East Africa - Brian W. Finch; R. Stratton Hatfield; Silvia Colombo; Adam S. Kennedy; Marije te Raa; Martin Irestedt; Dawid H. de Swardt; Joe Grosel; Derek Engelbrecht; Callan Cohen; Urban Olsson; Paul F. Donald; et al. (Journal of Ornithology, 2023)
We describe the discovery of a previously unknown population of Melodious Lark Mirafra cheniana from northern Tanzania and southern Kenya, some 2000 km north of what was previously thought to be its northern limit in central Zimbabwe. The identification of this population as M. cheniana is based primarily on analyses of mitochondrial DNA and song. We also clarify relationships within this genus by sequencing material of White-tailed Lark Mirafra albicauda for the first time; although its relationships with other species in the group remain unclear, our analyses clearly show it to be different from M. cheniana in the newly discovered population. The discovery of a population of M. cheniana in East Africa conforms to a known pattern for closely related lark species to have disjunct distributions in southern and eastern Africa.

Turgor loss point predicts survival responses to experimental and natural drought in tropical tree seedlings - Leonor Álvarez‐Cansino; Liza S. Comita; F. Andrew Jones; Eric Manzané‐Pinzón; Luke Browne; Bettina M. J. Engelbrecht (Ecology, 2022)
Identifying key traits that can serve as proxies for species drought resistance is crucial for predicting and mitigating the effects of climate change in diverse plant communities. Turgor loss point (π tlp ) is a recently emerged trait that has been linked to species distributions across gradients of water availability. However, a direct relationship between π tlp and species ability to survive drought has yet to be established for woody species. Using a manipulative field experiment to quantify species drought resistance (i.e., their survival response to drought), combined with measurements of π tlp for 16 tree species, we show a negative relationship between π tlp and seedling drought resistance. Using long‐term forest plot data, we also show that π tlp predicts seedling survival responses to a severe El Niño‐related drought, although additional factors are clearly also important. Our study demonstrates that species with lower π tlp exhibit higher survival under both experimental and natural drought. These results provide a missing cornerstone in the assessment of the traits underlying drought resistance in woody species and strengthen π tlp as a proxy for evaluating which species will lose or win under projections of exacerbating drought regimes.

Increased mortality of tropical tree seedlings during the extreme 2015–16 El Niño - Luke Browne; Lars Markesteijn; Bettina M. J. Engelbrecht; F. Andrew Jones; Owen T. Lewis; Eric Manzané‐Pinzón; S. Joseph Wright; Liza S. Comita (Global Change Biology, 2021)
As extreme climate events are predicted to become more frequent because of global climate change, understanding their impacts on natural systems is crucial. Tropical forests are vulnerable to droughts associated with extreme El Niño events. However, little is known about how tropical seedling communities respond to El Niño–related droughts, even though patterns of seedling survival shape future forest structure and diversity. Using long‐term data from eight tropical moist forests spanning a rainfall gradient in central Panama, we show that community‐wide seedling mortality increased by 11% during the extreme 2015–16 El Niño, with mortality increasing most in drought‐sensitive species and in wetter forests. These results indicate that severe El Niño–related droughts influence understory dynamics in tropical forests, with effects varying both within and across sites. Our findings suggest that predicted increases in the frequency of extreme El Niño events will alter tropical plant communities through their effects on early life stages.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Large uncertainties in future biome changes in Africa call for flexible climate adaptation strategies - Carola Martens; Thomas Hickler; Claire Davis‐Reddy; Francois Engelbrecht; Steven I. Higgins; Graham P. von Maltitz; Guy F. Midgley; Mirjam Pfeiffer; Simon Scheiter (Global Change Biology, 2021)
Anthropogenic climate change is expected to impact ecosystem structure, biodiversity and ecosystem services in Africa profoundly. We used the adaptive Dynamic Global Vegetation Model (aDGVM), which was originally developed and tested for Africa, to quantify sources of uncertainties in simulated African potential natural vegetation towards the end of the 21st century. We forced the aDGVM with regionally downscaled high‐resolution climate scenarios based on an ensemble of six general circulation models (GCMs) under two representative concentration pathways (RCPs 4.5 and 8.5). Our study assessed the direct effects of climate change and elevated CO 2 on vegetation change and its plant‐physiological drivers. Total increase in carbon in aboveground biomass in Africa until the end of the century was between 18% to 43% (RCP4.5) and 37% to 61% (RCP8.5) and was associated with woody encroachment into grasslands and increased woody cover in savannas. When direct effects of CO 2 on plants were omitted, woody encroachment was muted and carbon in aboveground vegetation changed between –8 to 11% (RCP 4.5) and –22 to –6% (RCP8.5). Simulated biome changes lacked consistent large‐scale geographical patterns of change across scenarios. In Ethiopia and the Sahara/Sahel transition zone, the biome changes forecast by the aDGVM were consistent across GCMs and RCPs. Direct effects from elevated CO 2 were associated with substantial increases in water use efficiency, primarily driven by photosynthesis enhancement, which may relieve soil moisture limitations to plant productivity. At the ecosystem level, interactions between fire and woody plant demography further promoted woody encroachment. We conclude that substantial future biome changes due to climate and CO 2 changes are likely across Africa. Because of the large uncertainties in future projections, adaptation strategies must be highly flexible. Focused research on CO 2 effects, and improved model representations of these effects will be necessary to reduce these uncertainties.

Examining the impact of multiple climate forcings on simulated Southern Hemisphere climate variability - Asmerom F. Beraki; Yushi Morioka; Francois A. Engelbrecht; Masami Nonaka; Marcus Thatcher; Nomkwezane Kobo; Swadhin Behera (Climate Dynamics, 2020)

Integrated climatology and trends in the subtropical Hadley cell, sunshine duration and cloud cover over South Africa - D. D. Mahlobo; T. Ndarana; S. Grab; F. Engelbrecht (International Journal of Climatology, 2019)
This study uses two methods to diagnose the local Hadley circulation; first the zonally averaged mass stream function, and second the stream function vector method. The two methods have been applied to the ERA‐Interim reanalysis data for the period 1979–2015, to calculate both the climatology and trends of the Hadley cell. Both diagnostics advocate downwards mass flux being dominant over the subtropics, particularly over South Africa, yet the strength of Hadley is seasonal. Contrasts have been found between linear trends of the two diagnostics. Zonally symmetric diagnostics indicate strengthening of the Hadley cell, particularly in the subtropics of the Southern Hemisphere in winter and weakening in summer. The zonally asymmetric results indicate maximum strengthening of the Hadley over South Africa to be in spring and weakening in summer. Furthermore, maximum decrease in cloud cover and increase in sunshine duration over South Africa is in spring, implying more opportunities for solar energy generation.

Assessing the impact of global changes on the surface water resources of southwestern Nigeria - A. O. Ayeni; E. Kapangaziwiri; A. S. O. Soneye; F. A Engelbrecht (Hydrological Sciences Journal, 2015)

Projected changes in tropical cyclone climatology and landfall in the Southwest Indian Ocean region under enhanced anthropogenic forcing - Johan Malherbe; F. A. Engelbrecht; W. A. Landman (Climate Dynamics, 2013)

Climate Change and Potato Production in Contrasting South African Agro-ecosystems 1. Effects on Land and Water Use Efficiencies - A. J. Haverkort; A. C. Franke; F. A. Engelbrecht; J. M. Steyn (Potato Research, 2013)

High‐resolution model‐projected changes in mid‐tropospheric closed‐lows and extreme rainfall events over southern Africa - C. J. Engelbrecht; F. A. Engelbrecht; L. L. Dyson (International Journal of Climatology, 2013)
Mid‐tropospheric closed‐lows (cold‐core cut‐off lows and warm‐core tropical lows) are important rain producing weather systems for the southern Africa region. Over South Africa, most wide‐spread flood events are caused by these systems. It is therefore important to explore the potential impact of anthropogenic forcing on the occurrence of closed‐lows and extreme rainfall events over the region. Coupled global circulation models (CGCMs) can not be directly applied for this purpose because of their relatively low spatial resolution—some form of downscaling is required to adequately resolve these systems and the rainfall they cause. In this study, a variable‐resolution atmospheric global circulation model is applied as a regional climate model to simulate closed‐low characteristics over southern Africa under current and future forcings. The model is forced with greenhouse gas concentrations according to the A2 SRES scenario and with sea surface temperatures (SSTs) and sea‐ice as specified by the CSIRO Mk3 CGCM. The model projects a general decrease in closed‐low frequencies over the region, which occurs in association with a general strengthening of the subsiding branch of the Hadley cell. However, the climate‐change signal shows variation in time and space and certain sub‐regions are projected to experience an increase in closed‐low frequencies during certain seasons. A general increase in extreme rainfall events is projected over southern Africa despite the projected decrease in closed‐low frequencies. It is deduced that this increase in extreme rainfall events is driven by intense convective rainfall events occurring within more frequently forming tropical‐temperate cloud bands. Over Mozambique, extreme rainfall events are projected to increase in association with more frequently occurring closed‐lows. Copyright © 2012 Royal Meteorological Society

Dynamics of the Conformal‐Cubic Atmospheric Model projected climate‐change signal over southern Africa - F. A. Engelbrecht; J. L. McGregor; C. J. Engelbrecht (International Journal of Climatology, 2009)
The projected climate‐change signal in simulations by the Conformal‐Cubic Atmospheric Model (CCAM) over southern Africa is presented, with particular emphasis on the projected changes in circulation over the region. Current (1975–2005) and future (2070–2100; A2 scenario) climate simulations are used for this purpose. In the austral winter of the future climate, frontal rain bands are displaced to the south as a result of the subtropical high‐pressure belt intensifying to the south of the subcontinent. In spring and autumn, mid‐ and upper‐level highs are simulated to become more prominent over the eastern and central parts of southern Africa. The enhanced subsidence associated with these systems results in generally lower rainfall totals over much of the south‐eastern subcontinent. To the north of these highs, enhanced westward moisture advection contributes to increased rainfall totals over northern Mozambique, whilst along the western periphery of the anomalously strong highs, enhanced southward moisture advection results in higher rainfall totals over Namibia, Botswana and the central and western interior of South Africa. In mid‐summer, the Indian Ocean High (IOH) is simulated to intensify most over the south‐western Indian Ocean (IO). This seemingly results in the more frequent occurrence of the cloud bands that constitute the South Indian Convergence Zone (SICZ) over the south‐eastern subcontinent—resulting in generally wetter conditions over this region. Copyright © 2008 Royal Meteorological Society

Simulating tick distributions over sub‐Saharan Africa: the use of observed and simulated climate surfaces - J. M. Olwoch; C. J. de W. Rautenbach; B. F. N. Erasmus; F. A. Engelbrecht; A. S. Van Jaarsveld (Journal of Biogeography, 2003)
Aim A broad suit of climate data sets is becoming available for use in predictive species modelling. We compare the efficacy of using interpolated climate surfaces [Center for Resource and Environmental Studies (CRES) and Climate Research Unit (CRU)] or high‐resolution model‐derived climate data [Division of Atmospheric Research limited‐area model (DARLAM)] for predictive species modelling, using tick distributions from sub‐Saharan Africa. Location The analysis is restricted to sub‐Saharan Africa. The study area was subdivided into 3000 grids cells with a resolution of 60 × 60 km. Methods Species distributions were predicted using an established multivariate climate envelope modelling approach and three very different climate data sets. The recorded variance in the climate data sets was quantified by employing omnidirectional variograms. To further compare the interpolated tick distributions that flowed from using three climate data sets, we calculated true positive (TP) predictions, false negative (FN) predictions as well as the proportional overlaps between observed and modelled tick distributions. In addition, the effect of tick data set size on the performance of the climate data sets was evaluated by performing random draws of known tick distribution records without replacement. Results The predicted distributions were consistently wider ranging than the known records when using any of the three climate data sets. However, the proportional overlap between predicted and known distributions varied as follows: for Rhipicephalus appendiculatus Neumann (Acari: Ixodidae), these were 60%, 60% and 70%; for Rhipicephalus longus Neumann (Acari: Ixodidae) 60%, 57% and 75%; for Rhipicephalus zambeziensis Walker, Norval & Corwin (Acari: Ixodidae) 57%, 51% and 62%, and for Rhipicephalus capensis Koch (Acari: Ixodidae) 70%, 60% and 60% using the CRES, CRU and DARLAM climate data sets, respectively. All data sets were sensitive to data size but DARLAM performed better when using smaller species data sets. At a 20% data subsample level, DARLAM was able to capture more than 50% of the known records and captured more than 60% of known records at higher subsample levels. Main conclusions The use of data derived from high‐resolution nested climate models (e.g. DARLAM) provided equal or even better species distribution modelling performance. As the model is dynamic and process based, the output data are available at the modelled resolution, and are not hamstrung by the sampling intensity of observed climate data sets ( c. one sample per 30,000 km 2 for Africa). In addition, when exploring the biodiversity consequences of climate change, these modelled outputs form a more useful basis for comparison with modelled future climate scenarios.